Diversity of sea cucumber from intertidal area of Pacitan and Bangkalan, East Java, Indonesia - ELSA DIANITA AULIA; FARID KAMAL MUZAKI; DIAN SAPTARINI; EDWIN SETIAWAN; DAVIN SETIAMARGA; ISWATUL DIAH LUTVIANTI; SANIAH KUSNATUR ROSYIDAH; NUR ALI MUHAMMAD (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Aulia ED, Muzaki FK, Saptarini D, Setiawan E, Setiamarga D, Lutvianti ID, Rosyidah SK, Muhammad NA. 2021. Diversity of sea cucumber from intertidal area of Pacitan and Bangkalan, East Java, Indonesia. Biodiversitas 22: 2136-2141. Sea cucumbers have an important role in the regeneration and mineralization processes of marine sediments. They are echinoderm, and their existence influences the sustainability of other organisms in different types of marine ecosystems. The objective of the present study was to determine the diversity of sea cucumber at Tawang and Pidakan coasts in Pacitan, and Labuhan coast in Bangkalan with slight differences in habitat characteristics. Sampling was conducted from 1000 m2 marked plots using hand collecting during low tide. Species richness, composition, abundance, and diversity indexes such as Shannon-Wiener’s diversity index (H’), Simpson’s dominance index (D) and Pielou’s evenness index (J) were observed. The results showed that there were 19 species found in this study, which belonged to family Stichopodidae, Holothuruidea, and Synaptidae. The highest species richness, abundance, H’ and J value was from Tawang coast. Value of H’ was 2.620 in Tawang, followed by 2.001 in Pidakan, and 1.621 in Labuhan. The highest D index was at Labuhan coast (0.223) compared with Tawang (0.085) and Pidakan (0.158) coast.